Effect of company size, liquidity and operational efficiency on bank profitability with problem credit risk as a moderating variable at commercial banks that are listed on the Indonesia Stock Exchange - Mohamad Adam; Riska Safitri; Tertiarto Wahyudi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study aims to measure and analyze the influence of company size, liquidity and operational efficiency on bank profitability with problem credit risk as a moderating variable at commercial banks that are listed on the Indonesia stock exchange. The unit of analysis in this study is 30 commercial banks listed on the official website of Bank Indonesia for the period 2012-2016. The type of data used is panel data with data analysis using purposive sampling method. The results of the study found that the size of the company negatively affected profitability, liquidity did not affect profitability, operational efficiency negatively affected profitability, company size positively affected problem credit risk, liquidity did not affect problem credit risk, operational efficiency had a positive effect on problem credit risk. problem credit risk has a positive effect on profitability.